Heroic past versus Un-heroic Present: The Politics of Memory and its Discontents - Potkonjak, Sanja (2008)
The aim of this paper is to cross-reference the discourse on antifascism and Europeanism. By presenting three Croatian art projects which are dealing with postsocialism, the paper focuses on institutional and everyday strategies of identity creation.
Projekt MZOS
ENG